Do executive functions and processing speed mediate the relationship between socioeconomic status and educational achievement? Analysis of an observational birth cohort study - Kate E. Mooney; Rachael W. Cheung; Sarah L. Blower; Richard J. Allen; Amanda Waterman (BMC Psychology)
Abstract Background There are large and persistent social inequalities in children’s educational attainment, with children from more socioeconomically disadvantaged families consistently having lower attainment. Despite this being widely reported, the mechanisms underlying the association between socioeconomic disadvantage and educational attainment are not well understood. It is important to understand the potential mechanisms by which socioeconomic disadvantage may impede on educational outcomes, as this knowledge could then be used to help target possible interventions to improve educational outcomes for socioeconomically disadvantaged children. Children’s executive functions (including working memory and inhibition) and processing speed abilities may underlie these inequalities, however, the previous literature regarding this is limited. This study examined longitudinal mediating mechanisms between socioeconomic status (SES) and educational achievement, using a socioeconomically deprived and ethnically diverse cohort. Methods Data from the Born in Bradford longitudinal cohort study was analysed using Structural Equation Modelling (n = 4201; 28% White British, 56% Pakistani heritage, 16% Other; 54% Female). SES was measured before birth, executive functions and processing speed were measured in middle childhood (Mage=8.45 years), and educational achievement was obtained through educational records (Mage=10.85 years). All models adjusted for child gender, age, language ability, ethnicity, and mother immigration status. Results Executive functions significantly mediated the association between SES and educational achievement (B = 0.109), whilst processing speed did not. Examination of executive function components revealed that working memory significantly mediated the associated between SES and educational achievement (B = 0.100), whilst inhibition did not. Working memory appeared to account for a large proportion (39%) of the total effect of SES on educational achievement. Conclusions These results, and the theoretical mechanisms linking working memory to educational achievement, both indicate the importance of finding ways to support children with working memory difficulties in the classroom. This is an important avenue for future research and may be useful for closing the socioeconomic gap in educational achievement.